Principal Leadership in Building Positive Culture in Elementary Schools: A Systematic Literature Review - Paryati Paryati; Meliya Faradisa; Kusfatun Yuliani; Siswadi Siswadi (Journal of Innovation and Research in Primary Education, 2026)
Positive culture in elementary schools constitutes a critical foundation for character development in the digital era, yet comprehensive understanding of principal leadership's specific role remains limited. This systematic literature review analyzed 47 peer-reviewed publications from 2015-2025 using PRISMA guidelines, employing thematic synthesis to identify leadership dimensions contributing to positive culture development. Analysis revealed six interconnected leadership dimensions: visionary direction setting (89% of studies), teacher empowerment through professional development (83%), effective communication (79%), exemplary modeling behavior (74%), digital leadership competence (60%), and collaborative culture development (emergent theme). Findings demonstrated that elementary contexts require distinct leadership approaches emphasizing concrete behavioral modeling and developmentally appropriate strategies. Digital leadership emerged as a contemporary imperative, though 73% of reviewed studies reported principals lacked adequate digital competencies. Unexpected findings included reciprocal empowerment dynamics between principals and teachers, and technology's paradoxical effects on school culture. Results extend transformational leadership theory by documenting elementary-specific patterns and implementation gaps between empowerment rhetoric and practice. Findings underscore urgent needs for comprehensive principal preparation programs addressing culture-building competencies, ongoing professional development supporting digital leadership capacity, and educational policies recognizing leadership stability as prerequisite for cultural transformation. Future research should employ longitudinal designs examining temporal dynamics and cross-cultural comparisons clarifying universal versus context-specific practices.